Kwestie praw człowieka w traktatach dwustronnych o dobrosąsiedztwie między Rzecząpospolitą Polską a Białorusią, Rosją i Ukrainą. Uwarunkowania polityczne - Leszczenko, Larysa (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The paper draws attention to the issues of human rights and freedoms as present in the content of the bilateral agreements concluded between Poland and its eastern neighbors. It pre-sents the analysis of the current political situation and the involvement of Poland and former Soviet countries in international processes during the early 1990s and discusses the influence of internal and external factors on the development of national human rights protection systems in the first years of the independence of Poland, Belarus, Russia and Ukraine. The content of bi-lateral agreements reflected the real political situation as well as the problems in the field of hu-man rights protection in the countries of the region. The absence of any monitoring mechanisms both in bilateral agreements and in international treaties referred to by the signatories of the for-mer agreements entails certain risks in the relations between Poland and its eastern neighbors. The loss of trust toward Russia due to its aggression against neighboring states forces the coun-tries in the region to strengthen their own military potential, as there is little reliance on the po-tency of bilateral agreements.
Keywords: Rosja; Polska; uwarunkowania polityczne; Ukraina; prawa człowieka; traktaty bilateralne; Białoruś